2022
DOI: 10.1038/s41598-022-18729-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intravenous dexmedetomidine on gastrointestinal function recovery after laparoscopic hysteromyomectomy: a randomized clinical trial

Abstract: Postoperative intestinal ileus is common after laparoscopic surgery, the incidence of those after hysterectomy was 9.2%. Anesthesia is one of the independent risk factors of postoperative ileus. Dexmedetomidine has been widely used in perioperative anesthesia and previous reports suggested that intraoperative dexmedetomidine may be associated with the improvement of gastrointestinal function recovery after abdominal surgery. We hypothesized that dexmedetomidine could improve gastrointestinal function recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Among mechanically ventilated patients with sepsis, sedation with DEX resulted in reduced inflammatory response and increased lactate clearance [ 46 , 47 ]. Intraoperative DEX reduced the time to first flatus, first oral feeding, and first defecation [ 48 ].These results showed that this treatment may be a feasible strategy for improving postoperative gastrointestinal function recovery in patients undergoing laparoscopic operation. With agreement, our results showed that the incidences of major postoperative complications including POPF, delayed gastric emptying and severe intra-abdominal infection were reduced in the DEX group though there were no statistical significance, which means further research is urgently needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among mechanically ventilated patients with sepsis, sedation with DEX resulted in reduced inflammatory response and increased lactate clearance [ 46 , 47 ]. Intraoperative DEX reduced the time to first flatus, first oral feeding, and first defecation [ 48 ].These results showed that this treatment may be a feasible strategy for improving postoperative gastrointestinal function recovery in patients undergoing laparoscopic operation. With agreement, our results showed that the incidences of major postoperative complications including POPF, delayed gastric emptying and severe intra-abdominal infection were reduced in the DEX group though there were no statistical significance, which means further research is urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Among mechanically ventilated patients with sepsis, sedation with DEX resulted in reduced inflammatory response and increased lactate clearance [46, 47]. Intraoperative DEX reduced the time to first flatus, first oral feeding, and first defecation [48]. These results showed that this treatment may be a feasible strategy for improving postoperative gastrointestinal function recovery in patients undergoing laparoscopic operation.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Previous studies have shown that dexmedetomidine provides effective postoperative early analgesia and reduced postoperative opioid requirements for different types of surgeries. [6][7][8][9] Furthermore, a meta-analysis indicated that dexmedetomidine relieved postoperative acute pain intensity and reduced perioperative analgesic consumption in neurosurgery, but the impact of dexmedetomidine on chronic pain needs further study. 10 It has been reported that postoperative acute pain correlates with an increased risk of chronic pain.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%
“…Published by Francis Academic Press, UK -43-support this view believe that dexmedetomidine can improve the activity of the vagus nerve, and then promote the peristalsis of the gastrointestinal tract. On this basis, the secretion function of the gastrointestinal tract is also enhanced, the digestive ability of food in the gastrointestinal tract is enhanced, and the desire to eat becomes more intense [27] . Scholars supporting another view believe that dexmedetomidine inhibited postoperative recovery of gastrointestinal function [28] .…”
Section: Effect On the Recovery Of The Gastrointestinal Tract Functionmentioning
confidence: 99%